2007
DOI: 10.1007/s00213-007-0707-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to intermittent nociceptive stimulation under pentobarbital anesthesia disrupts spinal cord function in rats

Abstract: Rationale-Spinal cord plasticity can be assessed in spinal rats using an instrumental learning paradigm in which subjects learn an instrumental response, hindlimb flexion, to minimize shock exposure. Prior exposure to uncontrollable intermittent stimulation blocks learning in spinal rats but has no effect if given before spinal transection, suggesting that supraspinal systems modulate nociceptive input to the spinal cord, rendering it less susceptible to the detrimental consequences of uncontrollable stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 56 publications
(76 reference statements)
0
27
0
Order By: Relevance
“…The traditional model of central sensitization focuses on NMDAR-mediated plasticity within the spinal cord and assumes that this process is regulated by both descending circuits and GABAergic inhibition (Gjerstad et al, 2001; Gwak and Hulsebosch, 2011; Washburn et al, 2007; Woolf, 2004). This general framework is supported by 20+ years of research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The traditional model of central sensitization focuses on NMDAR-mediated plasticity within the spinal cord and assumes that this process is regulated by both descending circuits and GABAergic inhibition (Gjerstad et al, 2001; Gwak and Hulsebosch, 2011; Washburn et al, 2007; Woolf, 2004). This general framework is supported by 20+ years of research.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern was observed by Weng et al (1998) who showed that bicuculline blocks central sensitization in halothane anaesthetized arthritic rats. Evidence suggests that pentobarbital anesthesia disrupts brain-dependent processes that normally counter the development of central sensitization (Washburn et al, 2007). This effect has been linked to serotonergic fibers that descend through the dorsolateral funiculus (DLF) (Crown and Grau, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When exposed to uncontrollable shock, the spinal cord develops a lasting impairment in behavioral plasticity (Grau et al, 1998; Crown and Grau, 2001; Crown et al, 2002b; Ferguson et al, 2003; Joynes and Grau, 2004; Patton et al, 2004; Ferguson et al, 2006; Washburn et al, 2007). Pharmacological activation of mGluRs mimicked the effects of uncontrollable shock, whereas mGluR antagonism at the time of training facilitated learning.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we employed the tailshock paradigm to also assess the effect of nociceptive stimulation on locomotor recovery following SCI. Subjects were treated with electrical stimulation 24 hours after surgery (modified from Washburn et al, 2007). They were loosely restrained in Plexiglas tubes as previously described (Crown et al, 2002a; Grau et al, 2004).…”
Section: Methodsmentioning
confidence: 99%